The role of government - (1) - Collas-Monsod, Solita (Philippine Journal of Public Administration, 1986)
Part of the difficulties experienced by the Philippines during the 20 years of Marcos rule stemmed both from lack of clear understanding of the exact role of government and limits of its power as well as failure to demand for and safeguard citizens' rights under a democratic system. There are specific roles which government could effectively assume and perform. These roles include: (1) coordinating economic activities; (2) promoting political stability and reducing uncertainty; and, (3) enhancing government's responsiveness to the needs of the people it governs.